2012
DOI: 10.1007/s00586-012-2213-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective therapy using granulocyte colony-stimulating factor for acute spinal cord injury: a phase I/IIa clinical trial

Abstract: These results indicate that intravenous administration of G-CSF (10 μg/kg/day) for 5 days is essentially safe, and suggest that some neurological recovery may occur in most patients. We suggest that G-CSF administration could be therapeutic for patients with acute SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 36 publications
0
57
0
Order By: Relevance
“…Moreover, it was reported that G-CSF attenuates peripheral NeP [11,12]. We recently conducted early-phase clinical trials to prove neuroprotective effects of G-CSF for SCI and acute aggravation of compressive myelopathy [13,14]. In the trial for compressive myelopathy, NeP was attenuated after G-CSF administration in 14/17 patients for several months.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, it was reported that G-CSF attenuates peripheral NeP [11,12]. We recently conducted early-phase clinical trials to prove neuroprotective effects of G-CSF for SCI and acute aggravation of compressive myelopathy [13,14]. In the trial for compressive myelopathy, NeP was attenuated after G-CSF administration in 14/17 patients for several months.…”
Section: Introductionmentioning
confidence: 97%
“…Our previous reports and several other recent studies have indicated that in addition to its hematopoietic effects, G‐CSF possesses nonhematopoietic functions and can be used as a potential drug for neurodegenerative diseases, including stroke and spinal cord ischemic, mechanical, and transection injuries . A phase I/IIa clinical trial of SCI has reported neurological improvement after G‐CSF administration . Based on primary safety endpoints of clinical trial IIa, Schabitz et al.…”
Section: Introductionmentioning
confidence: 99%
“…No significant differences were found, however, when comparisons were made to a database control group. 33 In a subsequent study in 37 participants with incomplete cervical SCI, Inada and coworkers 34 found that the same dose of G-CSF as used by Takahashi and colleagues 33 was associated with greater improvements in AIS motor scores than a control group at 1 year post-transplantation. Unfortunately, participants were allocated to the experimental group based on the institution they were treated at (in a nonrandomized manner), and it was not possible to assess whether clinical management differed between the sites.…”
Section: Strategies To Improve Motor Function Post-scimentioning
confidence: 99%
“…Greatest improvements were made by those classified AIS B at study entry. 32 Takahashi and colleagues 33 performed a Phase II study to assess the effects of granulocyte colony-stimulating factor (G-CSF), a compound shown to suppress neuronal apoptosis and expression of inflammatory cytokines. Sixteen participants injured less than 48 h before study enrollment received an intravenous dose of 10 lg/kg/ day for 5 consecutive days and demonstrated significant improvements in the ASIA Impairment Scale (AIS) motor scores on the follow-up assessment performed 3 months later when compared with the pre-intervention assessment.…”
Section: Strategies To Improve Motor Function Post-scimentioning
confidence: 99%